Ultrasound in the prediction of birthweight discordance in dichorionic twins - Lei, T; Zheng, J; Papageorghiou, AT; Feng, J-L; Lin, M-F; Zhang, F; Xie, H-N (Wiley, 2021)
Introduction Large birthweight discrepancy has been identified as a risk factor for perinatal morbidity and mortality in twin pregnancies. However, it remains unclear whether such discordance can be predicted by various biological indices with specific cut-off values, and how these depend on the gestational age. We aimed to determine the most effective way to predict large birthweight discordance at various gestational ages.